Parental Support towards Young Learner’s English Achievement - Saputra, Komang Yogi; Artini, Luh Putu; Utami, Ida Ayu Made Istri (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Teachers and parents must support students while studying at home because the problem with learning at home today is the lack of support and facilities. Lack of support and facilities can affect the learning process, greatly affecting the learning achievement of young people. The purpose of this study was to analyze the impact of intrinsic aspects of parental support such as education and parents' employment on children's English learning outcomes. This research is using mixed-method method. The subjects of this study were 5th grade elementary school students and their parents, totaling 31 people. Data search was carried out in two ways, namely surveys and interviews. The findings of this study indicate that parents with formal employment and a history of higher education provide 3 to 4 types of support to their children, while parents with informal employment and a history of low to secondary education provide 1 to 3 types of support. Based on the student's English score, the student with the highest score of 90, received 3 to 4 types of support from their parents. It can be concluded that parents' occupation and educational history of parents have an impact on providing support to children which has an impact on children's English learning outcomes.